IMPLEMENTASI STRATEGI KNOW WANT LEARNED (KWL) UNTUK MENINGKATKAN MEMBACA PEMAHAMAN PESERTA DIDIK DI SEKOLAH DASAR - Samsul Putri, Zeta Hazara; Yuliana, Rina; Rokmanah, Siti (JURNAL PENDIDIKAN DASAR, 2025)
Abstract: This research aims to find out whether the Know Want Learned (KWL) strategy can improve students' interpretative reading comprehension in elementary schools. The method used is a quasi-experimental quantitative method with a Nonequivalent Control Group Design. The sample for this research consisted of 25 class IV students at SDI Tahfidz Preneur Pagipon. The average value of the control class was pretest 61.2 and posttest 73.4. The experimental class was pretest 59.6 and posttest 78.4. The normality results for the control class pretest were 0.147 0.173, the control class posttest 0.153 0.173 and the experimental class pretest 0.139 0.173, the experimental class posttest 0.099 0.173. The homogeneity test results for the control and experimental class pretest scores were F count 1.774 and F table 1.983, the post test scores for the control and experimental classes were F count 1.365 and F table 1.983. The results of hypothesis testing obtained were Tcount 1.703 and Ttable 1.677 or tcount ttable, namely Ho was accepted and Ha was rejected with the results of the hypothesis reading interpretative comprehension who received the Know Want Learned (KWL) strategy treatment being better than students who received the Know strategy treatment Want to Learn (KWL). Likewise, the N-Gain results obtained by the experimental class were 0.48 with medium criteria which shows that after implementing the Know Want Learned (KWL) strategy there was an increase in students' interpretive reading comprehension in elementary schools.Keywords: Know Want Learned (KWL) Strategy, Reading ComprehensionAbstrak: Penelitian ini bertujuan untuk mengetahui apakah strategi Know Want Learned (KWL) dapat meningkatkan membaca pemahaman interpretatif peserta didik di sekolah dasar. Metode yang digunakan adalah metode kuantitatif jenis quasi eksperimen (eksperimen semu) dengan desain Nonequivalent Control Group Design. Sample penelitian ini berjumlah 25 peserta didik kelas IV SDI Tahfidz Preneur Pagipon. Hasil nilai rata-rata kelas kontrol adalah pretets 61,2 dan postets 73,4. Kelas eksperimen adalah pretest 59,6 dan postest 78,4. Hasil normalitas pretest kelas kontrol 0,147 0,173, posttest kelas kontrol 0,153 0,173 dan pretest kelas eksperimen 0,139 0,173, posttest kelas eksperimen 0,099 0,173. Hasil uji homogenitas nilai pretest kelas kontrol dan eksperimen adalah F hitung 1,774 dan Ftabel 1,983, nilai posttest kelas kontrol dan eksperimen adalah F hitung 1,365 dan Ftabel 1,983. Adapun hasil pengujian hipotesis yang didapatkan adalah Thitung 1,703 dan Ttabel 1,677 atau t hitung t tabel yaitu Ho diterima dan Ha ditolak dengan hasil hipotesis membaca pemahaman interpretatif yang mendapatkan perlakuan strategi Know Want Learned (KWL) lebih baik dengan peserta didik yang mendapatkan perlakuan strategi Know Want Learned (KWL). Begitupun hasil N-Gain yang di dapatkan kelas eksperimen adalah adalah 0,48 dengan kriteria sedang yang menunjukkan setelah menerapkan stratgi Know Want Learned (KWL) adanya peningkatan membaca pemahaman interpretatif peserta didik di sekolah dasar.Kata Kunci: Strategi Know Want Learned (KWL), Membaca Pemahaman